BACTOME—a reference database to explore the sequence- and gene expression-variation landscape of Pseudomonas aeruginosa clinical isolates. Issue Volume 47:Issue D1(2019) (1st October 2018) - Hornischer, Klaus; Khaledi, Ariane; Pohl, Sarah; Schniederjans, Monika; Pezoldt, Lorena; Casilag, Fiordiligie; Muthukumarasamy, Uthayakumar; Bruchmann, Sebastian; Thöming, Janne; Kordes, Adrian; Häussler, Susanne
Abstract: Extensive use of next-generation sequencing (NGS) for pathogen profiling has the potential to transform our understanding of how genomic plasticity contributes to phenotypic versatility. However, the storage of large amounts of NGS data and visualization tools need to evolve to offer the scientific community fast and convenient access to these data. We introduce BACTOME as a database system that links aligned DNA- and RNA-sequencing reads of clinical Pseudomonas aeruginosa isolates with clinically relevant pathogen phenotypes. The database allows data extraction for any single isolate, gene or phenotype as well as data filtering and phenotypic grouping for specific research questions. With the integration of statistical tools we illustrate the usefulness of a relational database structure for the identification of phenotype–genotype correlations as an essential part of the discovery pipeline in genomic research. Furthermore, the database provides a compilation of DNA sequences and gene expression values of a plethora of clinical isolates to give a consensus DNA sequence and consensus gene expression signature. Deviations from the consensus thereby describe the genomic landscape and the transcriptional plasticity of the species P. aeruginosa . The database is available at https://bactome.helmholtz-hzi.de .